An act additional to an "Act respecting the offices and duties of the Attorney General and county attornies." (Document (Maine. Legislature. Senate) ;, 1838)
1838 Senate bill amending an act regarding the duties and offices of the Attorney General and County Attorneys. Included were salaries, requirement of annual reports, and other matters.